2017
DOI: 10.1016/j.ssresearch.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Understanding trends in concentrated poverty: 1980–2014

Abstract: Trends in concentrated neighborhood poverty in the United States have been volatile over the past several decades. Using data from the 1980 to 2000 decennial census and the 2010-2014 American Community Survey, we examine the association between concentrated poverty across metropolitan areas in the United States and key proximate factors, including overall changes in poverty, racial residential segregation, and income segregation. One of our unique contributions is assessing the relative contribution of each of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 22 publications
2
56
0
Order By: Relevance
“…Finding that high levels of segregation were associated with STI diagnosis is supported by research showing elevated segregation exposes residents to socioeconomic disadvantages impacting an individual’s ability to properly care for their health [6, 11, 12, 2325]. Previous research also found segregation to be associated with area-level gonorrhea rates [6, 8] and risky sexual behaviors [9, 26].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Finding that high levels of segregation were associated with STI diagnosis is supported by research showing elevated segregation exposes residents to socioeconomic disadvantages impacting an individual’s ability to properly care for their health [6, 11, 12, 2325]. Previous research also found segregation to be associated with area-level gonorrhea rates [6, 8] and risky sexual behaviors [9, 26].…”
Section: Discussionmentioning
confidence: 94%
“…In addition, segregation has been associated with negative health outcomes among NHBs [810]. Segregation may also impact health through concentrated poverty [4, 11], which has been associated with neighborhood disadvantages such as unemployment, crime, and lower quality education opportunities [11–13]. Previous research has found segregation limits the availability of quality medical care and may make it difficult for residents to care of their health [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this point, we have argued that spatial inequality is a fundamental characteristic of rural poverty in the United States, and that variations among rural counties and between rural and urban areas are central dimensions of spatial inequality in the United States more broadly. In this article, we focus on one component of such inequality: Spatially concentrated poverty, or the high incidence of poverty in particular parts of the rural United States (Iceland and Hernandez 2017). We have multiple motivations for focusing on the geographic distribution of high-poverty areas and rural populations' exposure to such places.…”
Section: Why Spatially Concentrated Poverty Mattersmentioning
confidence: 99%
“…First, higher poverty rates are associated with higher concentration of poverty (Kneebone, Nadeau, and Berube, 2011; Iceland and Hernandez 2016). This is not surprising, as higher metropolitan area poverty rates would likely yield more higher-poverty neighborhoods and thus put more people at risk of living in such neighborhoods.…”
Section: Introductionmentioning
confidence: 99%